A novel fuzzy quality function deployment framework. Issue 1 (2nd January 2017) - Lee, Amy H. I.; Kang, He-Yau; Lin, Chun Yu; Chen, Jian-Shun
Abstract: To be competitive in an increasingly competitive global market with short product life cycles, firms today must perform innovative new product development (NPD) that can fulfil dynamic demands such as quality, performance and cost. Quality function deployment (QFD) has been a popular tool in real-practice applications. However, the conventional QFD has some limitations, such as how to generalize the opinions of multiple decision-makers, how to deal with a huge amount of subjective data, how to complete a large dimensional comparison and how to consider the ambiguity and uncertainty in human decision-making. This research, thus, aims to tackle the problems and develops a comprehensive model. The model integrates QFD with fuzzy set theory and decision-making methodologies, including Delphi method, decision-making trial and evaluation laboratory and analytic network process for implementing NPD project. A case study is carried out for a solar cell manufacturer. The proposed model can help designers systematically consider relevant NPD information and develop successful products.